Combination therapy with interferon and JAK1-2 inhibitor is feasible: Proof of concept with rapid reduction in JAK2V617F-allele burden in polycythemia vera - M.E. Bjørn (Leukemia Research Reports, 2014)
We report a 55 year old woman with post-ET PV for 12 years, who experienced resolution of severe constitutional symptoms within 3 days, a marked reduction in splenomegaly and a rapid decline in the JAK2V617F allele burden during combination therapy with interferon-alpha2a and ruxolitinib. Within 4 weeks the patient achieved complete hematological remission with normalization of peripheral blood counts and within 10 months the JAK2V617F-allele burden was reduced from 90% to 28%. Such a rapid decline in the JAK2V617F allele burden is highly unusual in PV-patients during low-dose IFN-alpha2 monotherapy and this finding warrants a prospective study with combination therapy.